2018
DOI: 10.1103/physrevlett.120.034503
|View full text |Cite
|
Sign up to set email alerts
|

Critical Bursts in Filtration

Abstract: Particle detachment bursts during the flow of suspensions through porous media are a phenomenon that can severely affect the efficiency of deep bed filters. Despite the relevance in several industrial fields, little is known about the statistical properties and the temporal organization of these events. We present experiments of suspensions of deionized water carrying quartz particles pushed with a peristaltic pump through a filter of glass beads measuring simultaneously the pressure drop, flux, and suspension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…Experiments (see Ref. [3]) have shown that the particle concentration is a crucial factor for the clogging and erosive behavior in deep bed filtration. Therefore we run a set of simulations where only C in is varied.…”
Section: Parameter Phase Spacementioning
confidence: 99%
See 3 more Smart Citations
“…Experiments (see Ref. [3]) have shown that the particle concentration is a crucial factor for the clogging and erosive behavior in deep bed filtration. Therefore we run a set of simulations where only C in is varied.…”
Section: Parameter Phase Spacementioning
confidence: 99%
“…Erosion in porous media plays an important role in a variety of systems, for example sand production in oil reservoirs [1,2] or breakthrough in water treatment plants. Bianchi et al [3,4] recently discovered that critical bursts in filters follow a power-law and studied their statistical properties. With a theoretical model we investigated these erosive bursts using computer simulations [5] and found that they occur when the local fluid pressure overcomes the forces keeping deposited matter in place and blocked pathways get unclogged.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other mechanism, high fluid pressures induce fracturing and/or unclogging of small pores and pore throats. Impulsive flushing events have been observed in a variety of settings and have been called erosive bursts [16,54]. In this framework, mechanical forces caused by fast local pore pressure variations [85] and/or rupture of brittle heterogeneities [30,58] may be responsible for LFEs.…”
Section: Introductionmentioning
confidence: 99%